Prevalence of Neospora caninum antibodies in sheep flocks of Uberlândia county, MG - Salaberry,Sandra Renata Sampaio (2010)
Neosporosis is a parasitic disease that occurs in sheep and is associated with reproductive failure. The aim of this study was to verify seroprevalence of Neospora caninum antibodies in 12 sheep flocks in Uberlândia county, Minas Gerais, Brazil, using Indirect Immunofluorescence Assay (IFA). A total of 334 sheep blood samples were analyzed and an epidemiologic questionnaire was applied for each farm in order to correlate with risk factors of neosporosis: gender, age, breed, abortion problems, contact with cattle and dogs, and presence of wild canids. The prevalence of Neospora caninum antibodies in sheep was 8.1%, with titers ranging from 50 to 3200 and 83.3% of farms detected at least one ovine reactive. There was statistically significant difference in flocks with abortion problems associated with the presence of Neospora caninum antibodies (p < 0.05).